Digital Transformation of MSMEs: Inclusion, Readiness, and Innovation Toward a Sustainable Economic Ecosystem - Sitorus, Sunday Ade; Siagian, Nalom; Steven, Orlando (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026DO - 10.14505/tpref.v17.1(37).04, 2026)
This study investigates the correlation between digital readiness, digital inclusion, and digital transformation with business model innovation and local economic sustainability among culinary MSMEs in Medan City. Using a quantitative approach grounded in the TOE Framework and DEIM model, data was collected from 250 respondents via structured questionnaires and analyzed using SEM-PLS. The findings reveal that digital readiness and digital inclusion significantly influence innovation in business models. Furthermore, the digital business ecosystem acts as a mediating variable impacting sustainable economic development. Practical implications include formulating community-based digital empowerment strategies and inclusive policy interventions.